Efektivitas Pembelajaran Basis Online di IAIN Tulungagung dengan Adanya Kebijakan Psychal Distancing Era Pandemi Covid 19 - Syahda Zahra, Alifarose; Wijayanti, Sherina (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2020)
This research focused on the effectiveness of online based-learning applications that are applied due to physical distancing policies. Physical distancing was applied by the Indonesian government as a preventive for the transmission of the COVID 19 virus, but it was not very successful because positive numbers continue to grow. COVID pandemic 19 changed various people's lifestyles in all fields including the education sector. The irony of the impact occurring in the education sector related to student finances which dropped dramatically without any income. There was news of a pseudo UKT 10% discount policy. This has decreased the spirit of students in learning because online learning uses a large quota. Various learning applications are gaining in popularity among students ranging from paid to not. Experiments on each application showed the advantages and disadvantages of each. Hadith Sciences students as a sample in this research responded that the application of Whatsapp was more effective. This research used purposive sampling by using a questionnaire as data collection material, and literature study as an approach model. The results of the research were: 1) Pillar of pandemic era bourgeois public unrest, 2) Discourse on UKT reduction policy, 3) Diffusion of online applications.